IMPLEMENTATION OF EDUCATIONAL PRACTICES IN THE MACHINE ENGINEERING SKILL PROGRAM AT SMK NEGERI 1 NANGGULAN KULON PROGO - Yusuf, Arya (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
Educational Practice (EP) is one of the activities organized by Yogyakarta State University for students in the education study program. The purpose of this EP is to provide practical experience to students in the field of education. EP is carried out in three stages: preparation, implementation, and evaluation. This activity is conducted at SMK Negeri 1 Nanggulan from November 2023 to January 2024. The research method used is descriptive qualitative with field studies in three stages: preparation, implementation, and evaluation. The results indicate that students gain valuable experience in teaching and engage in various non-teaching activities, as well as being able to overcome obstacles that arise during the implementation of EP. This experience is expected to be a useful asset for students in preparing themselves as professional educators.